Strategies to Strengthen Public Awareness Towards Handling Stunting Early - Sang Ayu Putu Rahayu; Rahayu Fery Anitasari; Kukuh Satria Wiratama (Universitas Negeri Semarang, 2025)
Stunting is basically chronic malnutrition and recurrent infections in children under five years old (toddlers) due to chronic malnutrition and recurrent infections. The problem of stunting is one of the essential issues in the world of children's health that is still a big concern, especially for children in underdeveloped and developing countries. The purpose of this article is to find a strategy to strengthen public awareness of handling stunting from an early age involving pregnant women, brides-to-be, and toddlers, especially teenagers. The service was carried out by collecting data by interviewing, observing, and reviewing documents. The results show that, basically, they understood the challenges in handling stunting. However, due to the lack of knowledge of both the community and village government officials, the stunting problem that occurs in the Village is often limited in the quality of efforts to solve it. In addition, the level of education results in people not caring or trying to find out about the good or wrong way to solve the stunting problem. The rise of stunting in the community also arises because people choose to allow this condition to occur and do not deter the source of the cause. It is as if the cause of stunting is so free to spread its impact without any pressure from the community, who are actually victims, to overcome it. Continuous support from various parties is needed to support efforts to handle stunting.